Consilio et animis : tracing a path to social justice through the classics - Ryan, Antoinette Maria (Emerald Publishing Limited : Information Age Pub., 2012)
Once the province and tool of élite learning in American society, and the core of the Humanities, the study of the Classics now occupies a tenuous place on the margins of curriculum in most public schools. Administrators of schools and districts with limited resources, teachers, and students of ancient Greek and Roman culture and language confront many questions regarding the relevance and utility of including the Classics in education that must address modern challenges.In this book, Toni Ryan argues that the Classics provide students with a uniquely wide range of opportunities for critical examination of the connections among language, cultural constructions of power and knowledge, and oppression in society. She proposes rationale for incorporating a critical approach to classical studies in American public schools as a path to exploring social justice issues. Critical pedagogy in Classics offers a platform for illuminating paths for critical awareness, reflection, and action in the quest to understand and address the broad concerns of social justice.Ryan asserts the potential for education in Classics to be reconstructed to empower and emancipate, particularly through the exploration of philosophical questions that have been pondered in classical cultures (and in classical studies) since antiquity. For public school educators and students, the examination of classical language and culture allows us to safely explore critical questions in an admittedly unsafe world. Those questions that are eternally ours, that are eternally centered in the human condition, are the province of Classics.
Keywords: Classical philology -- Study and teaching -- United States.; Classical literature -- Study and teaching -- United States.; Critical pedagogy -- United States.; Social justice -- Study and teaching -- United States.; Education -- Teaching -- General.; Teaching skills and techniques.; elektronické knihy; electronic books